Pengaruh Substitusi Tepung Kacang Hijau Terhadap KadarAmilosa Dan Mutu Tanak Beras Analog Talas - Riyanti, Lusi Adi (2016)
Background. Rice is the staple food consumed each day Indonesian society. The tendency of these communities to make local food in Indonesia underutilized. Thus the need for modification of foods analog rice slowly so that people can switch from rice to rice consumption analog. Rice is an analog artificial rice made from tubers with the addition of certain ingredients. The addition is made to improve the nutritional value of rice analog. One bulb that can be used in the manufacture of analog ie taro rice. Talas generally only used limited only fresh tubers. In the manufacture of analog taro rice used as flour and other ingredients are added mung bean flour and water were given additional materials, oils and gelatin. The addition of this material is intended to get the texture of the rice analog homogeneous . Objective. This study aims to determine the effect of mung bean flour substitution against amylose content and quality of rice analog talas. Research method. This study uses a randomized complete design with three variations of substitution and 3 repetitions of 5% , 10 % and 15 %. Result. The results showed that the highest amylose content is the substitution of 15% ie 10.06 % . And tanak highest quality is the substitution 15 is 279.73 % . Conclusion. There is no substitution effect mung bean flour to the amylose content and no substitute for the quality analog talas rice.